Physical dimension of the added signals in temporally defined schedules - SERRANO, MARIO; MORENO, SERGIO; CAMACHO, ISAAC; AGUILAR, FRANCISCO; CARPIO, CLAUDIO (Mexican Journal of Behavior Analysis, 2011)
Four groups of rats were exposed to temporally defined schedules (T = 60 s, tD = 30 s y tΔ = 30 s) in which tD and tΔ subcycles were correlated with exteroceptive signals belonging to either one or two physical dimensions: visualvisual, visual-auditory, auditory-visual, and auditory-auditory. Except for two rats in the visual-visual group, response rate was higher in tD than in tΔ. The response pattern within the T cycle show a maximal responding at the beginning of tD and few responses if any in the remainder of the cycle, except for the same two rats from the visual-visual group in which a scalloped pattern was observed during tΔ. Results are discussed in relation to similar experiments, highlight the effects of the interdimensional contrasts of the added signals.